2022
DOI: 10.1371/journal.pone.0273069
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of unsuccessful tuberculosis treatment outcome in Northern Red Sea region, Eritrea

Abstract: Background Eritrea has achieved the global target (90%) for tuberculosis (TB) treatment success rate. Though, events of unsuccessful TB treatment outcomes (death, treatment failure, lost to follow up and not evaluated) could lead to further TB transmission and the development of resistant strains. Hence, factors related to these events should be explored and addressed. This study aims to fill the gap in evidence by identifying the determinants of unsuccessful TB treatment outcomes in Eritrea’s Northern Red Sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…This increased risk could potentially be attributed to factors such as increased virulence of the MDR TB strain, longer treatment duration, expensive drugs, ineffective drug regimens, delayed diagnosis, and outdated treatment policies [16]. We found that TB patients co-infected with HIV had nearly three times the risk of death and a lower treatment success rate compared to HIV nonreactive patients, corroborated by several other studies [17,18]. This can be explained by the compromised immune state of the patients due to HIV infection, delayed presentation and diagnosis of HIV, poor adherence to both anti-retroviral therapy (ART) and anti-tubercular treatment (ATT), as well as the presence of other co-existing conditions like neoplasms and secondary infections [17].…”
Section: Discussionsupporting
confidence: 86%
“…This increased risk could potentially be attributed to factors such as increased virulence of the MDR TB strain, longer treatment duration, expensive drugs, ineffective drug regimens, delayed diagnosis, and outdated treatment policies [16]. We found that TB patients co-infected with HIV had nearly three times the risk of death and a lower treatment success rate compared to HIV nonreactive patients, corroborated by several other studies [17,18]. This can be explained by the compromised immune state of the patients due to HIV infection, delayed presentation and diagnosis of HIV, poor adherence to both anti-retroviral therapy (ART) and anti-tubercular treatment (ATT), as well as the presence of other co-existing conditions like neoplasms and secondary infections [17].…”
Section: Discussionsupporting
confidence: 86%
“…The longitudinal data of patients receiving care for TB enrolled in a surveillance program under the PNLT between 2017 and 2019 in Haiti were analyzed. Consistent with the findings of other studies, HIV-positive status was linked to poorer treatment outcomes [22] , [23] , [24] , [25] . In addition to the potential psychological effects of having to take several (HIV plus TB) pills, there are other arguments for this association.…”
Section: Discussionsupporting
confidence: 90%
“…Male patients with TB have a significantly lower chance of a successful outcome [24] . Although it is difficult to estimate the magnitude of the problem, during data quality workshops, some health care providers reported instances where male patients sell their food portions provided to them by the program instead of consuming them or used their transportation fees for other purposes, which may contribute to poor treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…These risk factors included variables known to be associated with unfavorable outcomes, such as alcohol abuse, age, and sex, among others. [13][14][15][16] Thus, the time period was a common determinant of both the treatment and the risk factors. However, the period should not be considered as a covariate because it overlapped with the treatment being evaluated.…”
Section: Discussionmentioning
confidence: 99%